Expression of a Synthetic Gene for the Major Cytotoxin (Cyt1Aa) of Bacillus thuringiensis subsp. israelensis in the Chloroplast of Wild-Type Chlamydomonas - Seongjoon Kang; Obed W. Odom; Candice L. Malone; Saravanan Thangamani; David L. Herrin (Biology, 2018)
Chlamydomonas reinhardtii (Chlamydomonas) strains that are toxic to mosquito larvae because they express chloroplast transgenes that are based on the mosquitocidal proteins of Bacillus thuringiensis subsp. israelensis (Bti) could be very useful in mosquito control. Chlamydomonas has several advantages for this approach, including genetic controls not generally available with industrial algae. The Bti toxin is produced by sporulating bacteria and has been used for mosquito control for >30 years without creating highly resistant mosquito populations. The suite of toxins is four main proteins: three Cry proteins and the cytotoxic Cyt1Aa (27 kDa). Cyt1Aa is not very toxic to mosquitoes by itself, but it prevents the development of resistance. The production of Cyt1Aa in other microbes, however, has been challenging due to its affinity for certain membrane phospholipids. Here we report on the production of recombinant Cyt1Aa (rCyt1A) in the chloroplast of photosynthetic Chlamydomonas at levels of at least 0.3% total protein. Live cell bioassays demonstrated toxicity of the rCyt1Aa Chlamydomonas to larvae of Aedes aegypti. We also expressed the chloroplast cyt1Aa gene in a wild-type Chlamydomonas strain (21 gr) that can grow on nitrate. These results have implications for developing a Chlamydomonas strain that will be toxic to mosquito larvae but will not induce strongly resistant populations.